Recruiting and exploring vulnerabilities among young people at risk, or in the early stages of serious mental illness (borderline personality disorder and first episode psychosis) - Gajwani, Ruchika; Wilson, Naomi; Nelson, Rebecca; Gumley, Andrew; Smith, Michael; Minnis, Helen (Frontiers in Psychiatry, 2022)
Introduction: Many gaps exist in our understanding of the developmental pathways to Severe Mental Illness (SMI), including borderline personality disorder (BPD) and psychosis. However, those who have experienced adverse childhood experiences (ACEs) are at an increased risk and there is evidence to suggest that one of the earliest markers is emotional dysregulation. An area which has received relatively less research attention is the role Neurodevelopmental Disorders (NDDs) play. The aim of this feasibility study was therefore to explore the clinical profiles of young people early in the course of SMI, including their profiles of ACEs, emotional regulation difficulties, borderline personality pathology traits and NDD’s. Methods: A cross-sectional study of young people (aged 15 to 25) at risk of SMI, currently being seen within NHS mental health services, was conducted. This included those with early symptoms of onset psychosis and/or early onset BPD as assessed by diagnostic interview. Eligible participants self-completed a battery of sociodemographic, clinical, and psychological measures in the company of a researcher. This included assessments of: symptoms of NDDs; borderline pathology traits; adverse childhood experiences; and difficulties in emotional regulation. Statistical analyses included Mann-Whitney U Tests and multiple regression. Results: Of the 118 potentially eligible participants who were referred, 48 were ultimately included in the study. Young people early in the course of SMI reported a high prevalence of ACE’s and deficits in emotional regulation. 79% met criteria for ADHD and/or ASD. Emotional dysregulation was found to significantly mediate the association between both ACE’s and the frequency of NDD’s and borderline personality pathology traits, however given the small sample size these results are preliminary in nature. Conclusion: Young people early in the course of SMI are at an increased risk of experiencing multiple childhood adversities and our results indicate a high prevalence of NDD’s amongst them. Emotional dysregulation emerged as a potentially significant early marker of future clinical severity. We suggest that the clinical implications of our findings include routine screening for NDD’s and ACE’s and an increased recognition of the significance of emotional dysregulation. However, larger scale longitudinal studies are needed to investigate these preliminary findings further.